Global burden and trends analysis of common cancers attributable to dietary risks from 1990 to 2021 and projection to 2050: a secondary analysis for the global burden of disease study 2021 - Wei, Tingting; Li, Yunhai; Zhang, Ze; Xu, Yijing; Huang, Hongbo; Huang, Ying; Li, Jiaying; Gong, Zheng; Hu, Zhiqi; Wang, Yichen; Zhang, Aijie; Li, Fan (Frontiers in Nutrition, 2025)
BackgroundDietary risk factors play crucial roles in the carcinogenesis and progression of cancer. However, the global burden of diet-related neoplasms (DRNs) remains underexplored.MethodsAge-standardized disability-adjusted life years (DALYs) and mortality rates for DRNs were extracted from the Global Burden of Disease (GBD) Study 2021. These were categorized by dietary risk, sex, age, and sociodemographic index (SDI) level. Predictions of DALY and mortality trends from 2021 to 2050 were generated via the Bayesian age-period-cohort models. Cross-country inequalities were assessed using the slope index of inequality and the concentration index.ResultsIn 2021, dietary risk contributed to 16.40 million DALYs and 0.67 million deaths from DRNs, including esophageal, stomach, colon and rectum, tracheal, bronchus, and lung, breast, and prostate cancers. Diets high in red meat and low in whole grains were primary dietary risks for DRNs. Globally, the age-standardized DALY and mortality rates related to DRNs have decreased over the past three decades and are projected to continue to decline until 2050. The DRNs burden is particularly heavy for colon and rectal cancer patients, patients in high and high-middle SDI regions, men, and those aged ≥70 years. Cross-country inequalities reveal that the slope index of inequality rose for DRNs from 262.74 in 1990 to 296.14 in 2021. The concentration index was 0.27 in 1990 and 0.30 in 2021.ConclusionThis study revealed significant variations in the burden of DRNs across different age groups, sexes, regions, and countries, emphasizing the potential for tailored cancer screening strategies targeting populations with higher risks of DRNs.